Glycoprotein gE of herpes simplex virus type 1: effects of anti-gE on virion infectivity and on virus-induced fc-binding receptors. - Para, M F (1982)
An Fc-binding glycoprotein, designated gE, was detected previously in cells infected with herpes simplex virus type 1 (HSV-1) and in virion preparations isolated from infected cells. For the studies reported here, we purified gE from HSV-1 strain HFEM(syn) by affinity chromatography and preparative electrophoresis and then immunized a rabbit to produce an antiserum to glycoprotein gE. We found that this antiserum selectively precipitated gE and its precursors from detergent-solubilized extracts of HSV-1 strain HFEM(syn)-infected HEp-2 cells, from extracts of other cell lines infected with the same virus, and from extracts of HEp-2 cells infected with several other HSV-1 strains. The antiserum did not precipitate any proteins from uninfected cells. The several forms of gE detected by immunoprecipitation accumulated in variable quantities in different cells infected with the different virus strains and also varied slightly with respect to electrophoretic mobility, suggesting some differences in the gE's from different HSV-1 strains and some effects of the host cell on the nature and extent of post-translational processing. One of the electrophoretic forms of gE previously detected in purified preparations of virions could be precipitated by anti-gE from extracts of purified HSV-1 strain HFEM(syn) virions. Moreover, anti-gE neutralized HSV-1 infectivity, but only in the presence of complement. Finally, F(ab')2 fragments of the anti-gE immunoglobulin partially inhibited the binding of 125I-labeled immunoglobulin G to the Fc receptors on HSV-1-infected cells.